2019
DOI: 10.3390/fib7100085
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Acoustic Performances of Resin Reinforced Biomass Fiber-Based Panel with Single and Multiple Tailed Cavity Inclusions for Interior Work

Abstract: The aim of this research is to observe the acoustic performance of absorber-based biomass fiber-reinforced polyester resins that were experimentally associated with the design of tailed cavity resonator inclusion, i.e., the cavities are partly in the form of a narrow slit. The model of electro-acoustic resonators and several treatments were developed and became the bases for understanding the changes of acoustic reactance in the new structure. Variations in the inclusion cavity and the addition of a narrow sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Higher number of pores on the fibre surfaces of EFB and MF treated with 3% of NaOH concentrations reduced the STL values compared to a few pores with only 2% of NaOH concentrations. Similarly, observations found by Setyowati et al [24], showed that kenaf fibre tend to have larger pores with channels appearing frequently on its surface than hemp fibre, which resulted in lower STL values for kenaf fibre than hemp fibre. EFB and MF treated with 3% of NaOH concentrations tend to have lower STL values than untreated fibre.…”
Section: Fig 5 -Stl For Efbsupporting
confidence: 68%
“…Higher number of pores on the fibre surfaces of EFB and MF treated with 3% of NaOH concentrations reduced the STL values compared to a few pores with only 2% of NaOH concentrations. Similarly, observations found by Setyowati et al [24], showed that kenaf fibre tend to have larger pores with channels appearing frequently on its surface than hemp fibre, which resulted in lower STL values for kenaf fibre than hemp fibre. EFB and MF treated with 3% of NaOH concentrations tend to have lower STL values than untreated fibre.…”
Section: Fig 5 -Stl For Efbsupporting
confidence: 68%
“…Setyowati et al concluded that the natural fibers in the composite are the potential to be implemented in architectural acoustics due to their specifications on reducing the sound energy absorption in certain frequencies [1], [2]. Figure 3 describes the performance of sound absorption of materials, which principally occur as the poor absorber.…”
Section: Sound Absorption Coefficientmentioning
confidence: 99%
“…This research not only focuses on porous hexagonal ceramic innovation by using water hyacinth powder in clay mixtures, in that it has the ability of absorption and material insulation but also compares the acoustic performance of porous ceramic with water hyacinth-based composites obtained in previous studies [1]. Meanwhile, several studies on acoustic materials from natural materials have also been carried out [2], [3].…”
Section: Introductionmentioning
confidence: 99%
“…Noise refers to sound that interferes with the surrounding living environment, such as industrial noise [1], construction noise [2], traffic noise [3] and social activity noise [4]. Normally, the actual noise is in a wide frequency region [5], which requires the utilized sound absorber to be broadband [6][7][8][9][10]. Heo et al [6] utilized acoustic metasurfaces (AMSes) with high reflective characteristics to achieve significant noise reduction in tirepavement interactions over a broadband of acoustic frequencies under 1000 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…A novel sound absorber of acoustic metamaterial by the parallel connection of multiple spiral chambers that exhibit an extraordinarily low-frequency sound absorption performance in the frequency range of 360-680 Hz has been proposed by Duan et al [8], which was prepared by the low-force stereolithography of the photopolymer resin. Setyowati et al [10] studied the sound absorption performance of absorber-based biomass fiber-reinforced polyester resins, and it showed that a sample of a 15 mm single-tailed cavity kenaf fiber had a higher sound absorption and wider broadband frequencies than the hemp fiber, with a peak on 0.31-0.32 between 1.00-2.00 kHz. The achievement of broad low-frequency sound absorption performance promotes the application of acoustic metamaterials.…”
Section: Introductionmentioning
confidence: 99%